PERTANGGUNGJAWABAN PIDANA OLEH ANAK SEBAGAI PELAKU TINDAK PIDANA PENCURIAN DI PENGADILAN NEGERI BANTUL YOGYAKARTA - Muhamat Burhan; Harti Winarni (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to understand the implementation of criminal liability for minors who commit theft at the Bantul District Court in Yogyakarta, as well as the factors influencing the application of criminal sanctions against such children. The research employs an empirical juridical method with a qualitative approach. Data were collected through literature studies and direct interviews with judges handling juvenile cases. The findings indicate that the legal process for minors is carried out by prioritizing the principle of restorative justice through a diversion mechanism, in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Diversion is conducted prior to trial, and if it fails, the court proceedings continue behind closed doors with consideration of the best interests of the child. The imposed sanctions are more rehabilitative in nature, such as returning stolen goods, compensation, or guidance by parents. Factors influencing the imposition of sanctions include internal factors related to the child, external conditions such as family and environment, as well as legal aspects and recommendations from the Correctional Center (BAPAS).